Modelling and control of ACMV systems - Ong, Tai Fu (Nanyang Technological University, 2020)
Energy-saving and improvement of system efficiency have recently been some of the most important considerations when designing buildings. Among various energy consumers of buildings, the Air-Conditioning and Mechanical Ventilation (ACMV) system happens to be the largest energy consumer of the buildings. Among the various types of ACMV systems out in the market, a new and innovative type of system known as thermosiphon beam can help to reduce the energy consumption of the ACMV system. In this project, investigation on how various operating conditions, such as room temperature, chilled water flow rate and chilled water inlet temperature, will affect the cooling capacity of the thermosiphon beam will be performed. Additionally, investigations will be conducted to determine how different length of cross flow fan will affect the air flow that enters the cooling coil of the thermosiphon beam. These experiments provide a better understanding on how different operating conditions lead to various effects on the cooling capacity of the thermosiphon beam, hence allowing the thermosiphon beam to be operated and controlled at its highest efficiency level.